Case report title information: Adnexal torsion in a premenarchal female with absence of contralateral ovary and fallopian tube - Alexis Svokos; Mackenzie Ferry; Brytanie Marshall; Deanna Mascho-Cawley (Elsevier, 2020)
We report the case of a 9-year-old pre-menarchal female who presented with acute onset abdominal pain and findings concerning for left adnexal torsion. At the time of surgical intervention the patient was found to have absence of the contra-lateral ovary and fallopian tube. Awareness of the possibility of concomitant adnexal torsion and contralateral tubo-ovarian absence would help clinicians manage patients who present with similar symptoms. In such cases, early surgical intervention and ovarian preservation is critical, while delay in treatment can render the patient infertile.